The surface-exposed PA51-72-loop of the influenza A virus polymerase is required for viral genome replication - Nilsson-Payant, B; Sharps, J; Hengrung, N; Fodor, E (American Society for Microbiology, 2018)
The heterotrimeric influenza A virus RNA-dependent RNA polymerase complex, composed of PB1, PB2 and PA subunits, is responsible for transcribing and replicating the viral RNA genome. The N-terminal endonuclease domain of the PA subunit performs endonucleolytic cleavage of capped host RNAs to generate capped RNA primers for viral transcription. A surface-exposed flexible loop (PA51-72-loop) in the PA endonuclease domain has been shown to be dispensable for endonuclease activity. Interestingly, the PA51-72-loop was found to form different intramolecular interactions depending on the conformational arrangement of the polymerase. In this study, we show that a PA subunit lacking the PA51-72-loop assembles into a heterotrimeric polymerase with PB1 and PB2. We demonstrate that in a cellular context the PA51-72-loop is required for RNA replication but not transcription by the viral polymerase. In agreement, recombinant viral polymerase lacking the PA51-72-loop is able to carry out cap-dependent transcription but is inhibited in de novo replication initiation in vitro. Furthermore, vRNA synthesis is also restricted during ApG-primed extension, indicating that the PA51-72-loop is required not only for replication initiation but also for elongation on a cRNA template. We propose that the PA51-72-loop plays a role in the stabilisation of the replicase conformation of the polymerase. Together, these results further our understanding of influenza virus RNA genome replication in general and highlight a role of the PA endonuclease domain in polymerase function in particular.